21st Century Early Adult (55-74) Deaths from Brain-Disease-Deaths Compared to All Other Cause Mortality in the Major Western Countries – Exposing a Hidden Epidemic. (2nd November 2021) - Pritchard, Colin; Hansen, Lars; Silk, Anne; Rosenorn-Lanng, Emily
ABSTRACT: Objectives: To examine early adult deaths (EAD) – people aged 55–74 due to brain disease deaths (BDD) compared to all other causes (AOC) in the 21st century in 21 major Western countries (MWC). Method: EAD are below MWCc average life expectancy. All mortality drawn from the latest WHO data. The three global BDD categories consist of mental and behaviour disorder, nervous diseases and Alzheimer and other dementias. Mortality rates per million are analysed for people 55–74 years and total age-standardised death rates (ASDR). BDD rates between 2000–2015 compared against AOC of deaths for EAD and ASDR. Confidence Intervals determine any significant difference AOC and BDD over the period 2000–15, plus an examination of EAD in six separate global mortality categories. Results: EAD : The separate BDD categories for EAD significantly positively correlated, validating their combination as BDD. Every country's AOC 55–74 rates fell substantially, but fourteen country's BDD rose substantially (>20%) and all MWC countries BDD rose significantly more than AOC. ASDR : All nations total AOC fell substantially, whereas seventeen BDD rates rose substantially and every country's BDD significantly increased compared to AOC deaths. Six other EAD mortalities, circulatory, cancer, respiratory, compared to BDD produced Odds Ratios ranging from 1:1.54 to 1:2.36 such were the marked differences over the period. Discussion: Positive news is that AOC are down across all investigated countries in the 21st century. However, the extent of the EAD rises in just 16 years indicates that these BDD conditions are starting earlier suggesting multiple interactive environmental factors impacting upon brain related diseases.